2022
DOI: 10.1002/ldr.4451
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive assessment of pollution indices, sources apportionment and ecological risk mapping of heavy metals in agricultural soils of Raebareli District, Uttar Pradesh, India, employing a GIS approach

Abstract: In the environment, heavy metal contamination is a well known problem due to its persistence and toxicity. Heavy metal pollution has significantly affected soil properties and functions, resulting in significantly increased land degradation as a result of anthropogenic interventions that include mining and various industrial and agriculture activities. While heavy metals pollution in soil have been studied very rarely in this District, this paper explores the current status of agricultural soil pollution by he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 118 publications
0
6
0
Order By: Relevance
“…For non‐structural degradation, Neeraj et al (2023) reported the role of heavy metal pollution in influencing soil fertility in different locations in north India (Neeraj et al, 2023). In another study, Thakur et al (2022) use satellite data (LANDSAT‐5 and 8) to report a substantial increase in degradation of forest ecosystems due to open and closed mining activities in central India.…”
Section: Review Of Papers Published In This Issuementioning
confidence: 99%
“…For non‐structural degradation, Neeraj et al (2023) reported the role of heavy metal pollution in influencing soil fertility in different locations in north India (Neeraj et al, 2023). In another study, Thakur et al (2022) use satellite data (LANDSAT‐5 and 8) to report a substantial increase in degradation of forest ecosystems due to open and closed mining activities in central India.…”
Section: Review Of Papers Published In This Issuementioning
confidence: 99%
“…The soils examined in the study had a range of bulk density values, which varied with depth, texture, and organic matter content, with an average of 1.5 gcm À3 . The pH of the soils was found to be neutral to slightly or moderately alkaline, with pH levels ranging from 7.08 to 8.9 (Neeraj et al, 2023). The reduction in soil organic matter (SOM) in agricultural soils is a serious threat to food safety worldwide, caused by intensive land use, inappropriate soil management practices, and overuse of chemical inputs (Karmegam et al, 2019).…”
Section: Physicochemical Properties Of All Sampling Sitesmentioning
confidence: 99%
“…They can also be used for statistical analysis in order to evaluate sources of pollution 36 or to characterise soils 21 , 37 . In another line of research, the dataset can be used to establish soil pollution indices 38 or to determine ecological risk 39 . By determining the per capita consumption of the food crops in the local area, we can evaluate the health risk associated with exposure to toxic metals 40 and establish regulatory reference values for public policy and food innocuity decisions 41 , 42 .…”
Section: Background and Summarymentioning
confidence: 99%